Induction of Twisting Disease Resistance on Shallot (Allium cepa var. ascalonicum) Against Twisting Disease (Fusarium oxysporum f. sp. cepae) through Biopesticide Application - Wiyatiningsih, Sri; Santoso, Wahyu; Wijaya, Riko Setya; Wijayanti, Fitri (Universitas Panji Sakti, 2024)
This study aimed to develop resistance in shallot (Allium cepa) against twisting disease caused by Fusarium oxysporum by applying microorganism-based biopesticides. By inducing resistance in shallots, the research sought to explore the pathogen-host interactions, understand infection mechanisms, and establish sustainable disease management strategies. Utilizing a biopesticide approach within an organic farming framework, this study aimed to assess the effectiveness of biopesticides in inducing plant defense mechanisms. The experimental design was non-factorial and followed a randomized block structure, consisting of four treatments with three replications each: (A) Chemical pesticide and fertilizer, (B) Biopesticide applied to seeds and plants, with chemical fertilizers on soil, (C) Soil sterilization with biopesticide and pesticide application on plants, and (D) Soil sterilization with biopesticide, with biopesticide applied to seeds and plants. Observations focused on disease intensity and salicylic and jasmonic acid levels in shallot bulbs. Results demonstrated that biopesticide application successfully reduced disease incidence and increased resistance, as shown by higher levels of salicylic and jasmonic acids in treated plants. The study concluded that biopesticides are promising for enhancing systemic resistance in shallots.